2021
DOI: 10.3390/cancers13215498
|View full text |Cite
|
Sign up to set email alerts
|

ATM Kinase Dead: From Ataxia Telangiectasia Syndrome to Cancer

Abstract: ATM is one of the principal players of the DNA damage response. This protein exerts its role in DNA repair during cell cycle replication, oxidative stress, and DNA damage from endogenous events or exogenous agents. When is activated, ATM phosphorylates multiple substrates that participate in DNA repair, through its phosphoinositide 3-kinase like domain at the 3′end of the protein. The absence of ATM is the cause of a rare autosomal recessive disorder called Ataxia Telangiectasia characterized by cerebellar deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…In addition, knockdown of the zebrafish arpc1b gene resulted in reduced embryonic T cells and thrombocytes [ 42 ], recapitulating human ARPC1B deficiency [ 74 ]. Ataxia-telangiectasia (A-T) syndrome is a human disorder characterized by neurodegeneration, immune dysregulation, cancer susceptibility and premature aging and results from defects in the ATM gene [ 43 ]. Zebrafish LOF atm mutants exhibited similar phenotypes, with multi-lineage immunodeficiency along with motor disturbances and cancer predisposition [ 75 ].…”
Section: Zebrafish Models Of Lymphoid Disordersmentioning
confidence: 99%
“…In addition, knockdown of the zebrafish arpc1b gene resulted in reduced embryonic T cells and thrombocytes [ 42 ], recapitulating human ARPC1B deficiency [ 74 ]. Ataxia-telangiectasia (A-T) syndrome is a human disorder characterized by neurodegeneration, immune dysregulation, cancer susceptibility and premature aging and results from defects in the ATM gene [ 43 ]. Zebrafish LOF atm mutants exhibited similar phenotypes, with multi-lineage immunodeficiency along with motor disturbances and cancer predisposition [ 75 ].…”
Section: Zebrafish Models Of Lymphoid Disordersmentioning
confidence: 99%
“…Homozygous or compound heterozygous ATM GPVs cause a rare autosomal recessive disorder called A-T, characterized by progressive cerebellar ataxia, telangiectasia, oculomotor apraxia, immunodeficiency, cancer susceptibility, and radiation sensitivity [118]; therefore, counseling ATM GPV carriers against the risk of autosomal recessive conditions in their offspring is recommended [14].…”
Section: Prevalence and Risk Of Developing Cancersmentioning
confidence: 99%
“…ATM GPV heterozygous carriers have an increased risk for several types of cancers, including breast, ovarian, and pancreatic cancers [ 46 , 68 ]. However, the carriers of biallelic ATM GPVs are affected by ataxia–telangiectasia (AT, OMIM #208900), which is a rare autosomal recessive syndrome characterized by progressive cerebellar ataxia, cutaneous telangiectasias, increased risk of developing hematologic and solid tumors, and immunodeficiency [ 66 , 68 , 69 ].…”
Section: Atm (Ataxia–telangiectasia Mutated) Genementioning
confidence: 99%
“…A recent meta-analysis [ 45 ] reported the prevalence of ATM GPVs in patients with EOC to be 0.6767% (26/3842 cases) and showed a significant association between ATM GPVs and EOC (odds ratio (OR) = 1.977, 95% confidence interval (CI) = 1.330–2.939) ( Table 1 ). Another population-based cohort study reported that the prevalence of ATM GPVs was 0.57–0.64% [ 18 , 69 ]. The absolute lifetime risk of EOC estimated by the NCCN clinical practice guidelines in oncology is <3% [ 26 , 46 ].…”
Section: Atm (Ataxia–telangiectasia Mutated) Genementioning
confidence: 99%